Physiochemical properties evaluation of Calophyllum inophyllum biodiesel for gas turbine application - Fauzan N.A.; Tan E.S.; Pua F.L.; Muthaiyah G. (Elsevier B.V., 2023)
The devastating phenomenon of depletion of fossil fuel and environmental pollution have caught global concern to explore for alternative fuel resources that could meet human demand. Due to the properties that match diesel fuel properties, biodiesel appears to be one of the plausible resources due to the many advantages it provides compared to the conventional petroleum-diesel. Recently, non-edible oil receives worldwide attention compared to edible feedstock in producing biodiesel. Among the many privileges provided by non-edible Calophyllum inophyllum plant include useful by-products (glycerol), environmental friendly, ability to reduce the competition for food and more economical feedstock. Besides the application in the diesel engine, biodiesel could be a promising substitute to distillate fuel for power generation sector. Gas turbine develops steady flame during its combustion and this feature gives the flexibility of wide range of fuel selection including biodiesel for gas turbine. Therefore, the use of biodiesel in gas turbine seems a viable solution for the problems. This paper aims to evaluate the physiochemical properties of C. inophyllum (CI) biodiesel for gas turbine application. The properties of C. inophyllum methyl ester was obtained to evaluate its potential in gas turbine application according to the fuel selection standard for gas turbine; ASTM D2880. The evaluation result show that C. inophyllum biodiesel may be pursued as an alternative fuel in gas turbine. 2020 The Author(s)